The Impact of physical activity and related factors on the risk of melanoma development and progression of the disease - A literature review - Joanna Szuba; Magdalena Rędaszka; Oliwia Barańska; Małgorzata Chańko; Justyna Drożdżał; Adam Krzaczkowski; Emilia Niedzieska; Zofia Szular; Tymon Wojczulis; Katarzyna Ziemek (Quality in Sport, 2025)
Introduction